The Effectiveness of Promotion Agencies at Attracting Foreign Direct Investment - Morisset, Jacques; Andrews-Johnson, Kelly (Washington, DC: World Bank, 2013)
A perplexing question has become increasingly important: Does investment promotion really work? The authors hereby made a major step in providing a convincing answer to this question. Because many countries were not yet trying to promote investment, the authors could conduct a very simple test: compare foreign direct investment (FDI) flows into countries that had promotion activities in the United States, with the flows into countries that didn't. The study provided some crude support for the idea that promotion worked and, with some assumptions, the costs of attracting an investor, or its trade-off seemed to favor promotion. But more recent data from this survey provided the authors a more sophisticated methodology; as a result, their study is more convincing, and addresses many more questions than earlier work. They find the median expenditure on investment by developing countries to be smaller than expected. However, the study shows that expenditures below a certain annual level yield few, if any returns. Where the investment climate is bad, efforts to improve policy seem sensible; but in fact, in countries with very poor investment climates, returns to expenditures on other promotion activities are likely to be especially low. Similarly, it is likely that promotion has more impact on certain kinds of investors than on others. The research stipulates important factors about organizational issues, and, results show that agencies with some kind of participation from the private sector, do better than those that are purely governmental. It also provides evidence to suggest that, at least for many countries, a dollar spent on investment promotion yields a better return than a dollar provided as a subsidy or given up through a tax incentive program.